Traffic Law Enforcement on Illegal Racing at Tulungagung Police Realizing Kamseltibcarlantas - Susetyo, Dhafa Prabaswara; Farhan, Lazuardhy; Shidqy Fauzan, Muhammad (Tanggon Kosala, 2025)
The rampant street racing activities in Tulungagung Regency raise concerns within the community. This paper discusses the law enforcement of street racing activities by the Tulungagung Police Department to realize road safety and traffic order (Kamseltibcarlantas), along with the influencing factors. The discussion encompasses the concepts of traffic, street racing, violation enforcement, and road safety. Qualitative methods employing data triangulation from primary, secondary, and tertiary sources involve data collection, reduction, presentation, and verification. The research findings indicate that law enforcement against street racing in the jurisdiction of the Tulungagung Police Department is carried out through a combination of non-penal (preventive and preemptive) and penal (repressive) approaches. Non-penal approaches include initiatives like "Police goes to school" and patrols, while penal measures involve law enforcement actions such as fines and criminal sanctions. Factors influencing traffic law enforcement against street racing include legal aspects, law enforcement agencies such as the Tulungagung Police Traffic Unit, infrastructure and facilities aiding law enforcement efforts, public response, and cultural alignment with regulations. The enforcement of traffic law against street racing activities in the Tulungagung Police Resort involves both non-penal and penal approaches. Factors such as laws, law enforcement officers, infrastructure, community, and culture influence its implementation.